Recombinant factor VIII Fc fusion protein for the treatment of severe haemophilia A: Final results from the ASPIRE extension study. Issue 3 (30th March 2020) - Nolan, Beatrice; Mahlangu, Johnny; Pabinger, Ingrid; Young, Guy; Konkle, Barbara A.; Barnes, Chris; Nogami, Keiji; Santagostino, Elena; Pasi, K. John; Khoo, Liane; Winding, Bent; Yuan, Huixing; et al.
Abstract: Introduction: The efficacy and safety of recombinant factor VIII Fc fusion protein (rFVIIIFc) as an extended half‐life treatment for severe haemophilia A were demonstrated in the Phase 3 A‐LONG and Kids A‐LONG studies. Eligible subjects who completed A‐LONG and Kids A‐LONG could enrol in ASPIRE (NCT01454739), an open‐label extension study. Aim: To report the long‐term safety and efficacy of rFVIIIFc in subjects with severe haemophilia A who enrolled in ASPIRE. Methods: Previously treated subjects received one or more of the following regimens: individualized prophylaxis (IP), weekly prophylaxis, modified prophylaxis or episodic treatment. Subjects could switch treatment regimen at any time. The primary endpoint was inhibitor development. Results: A total of 150 subjects from A‐LONG and 61 subjects from Kids A‐LONG enrolled in ASPIRE. Most subjects received the IP regimen (A‐LONG: n = 110; Kids A‐LONG: n = 59). Median (range) treatment duration in ASPIRE for subjects from A‐LONG and Kids A‐LONG was 3.9 (0.1‐5.3) years and 3.2 (0.3‐3.9) years, respectively. No inhibitors were observed (0 per 1000 subject‐years; 95% confidence interval, 0‐5.2) and the overall rFVIIIFc safety profile was consistent with prior studies. For subjects on the IP regimen, annualized bleed rates (ABR) remained low (median overall ABR for adults and adolescents was <1.0) and extended‐dosing intervals were maintained (median of 3.5 days) for the majority of subjects in ASPIRE. Conclusion: ASPIRE results, which include up to 5 years of follow‐up data, confirm earlier reports on the consistent and well‐characterized safety and efficacy of rFVIIIFc treatment for severe haemophilia A.